Impact of Life Skills on Leadership Development - Vashishtha, Kriti (International Journal of Social Sciences and Management, 2015)
Life skills are basically the psychosocial skills which include personal, social, interpersonal, cognitive and affective components on an individual. For a better life one needs to have better decision making and problem solving skills. If any head or leader posses these characteristics then his/her tasks of making his/her leadership effective also becomes easy. Present study aims to see the impact of life skills sessions on problem solving and decision making attitude of school level leaders. For this purpose, 150 students were selected from 10 different schools. The age group ranged between 16-18 years. It is a pre and post test study. After taking the pre-test of the students (head/leaders) on the basis life-skills questionnaire by NCERT, the students were provided with 10 life-skills sessions (5 on problem solving and 5 on decision making, one session per day). After the sessions, the same questionnaire was administered on the students. On the basis of students’ response, t-test was applied and results have showed a significant enhancement in the skills of decision making and problem solving in the leaders. Int. J. Soc. Sci. Manage. Vol-2, issue-3: 273-274 DOI: http://dx.doi.org/10.3126/ijssm.v2i3.12650